2012
DOI: 10.1111/j.1464-410x.2012.11046.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal lesions with low R.E.N.A.L nephrometry score are associated with more indolent renal cell carcinomas (RCCs) or benign histology: findings in an Australian cohort

Abstract: OBJECTIVE• To validate the relationship of the R.E.N.A.L nephrometry score to histological features of renal lesions treated by surgical excision by radical nephrectomy (RN) or nephron-sparing surgery (NSS) at an Australian tertiary referral centre. PATIENTS AND METHODS• Patients undergoing surgery between 2005 and 2009 with imaging studies available were included.• The R.E.N.A.L. nephrometry score is an objective measure of factors important in determining suitability for NSS, e.g. size, exophytic nature, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 10 publications
3
22
0
1
Order By: Relevance
“…Second, RNS was significantly correlated with histological findings of renal masses, as previously shown in other studies . Recent advances in imaging technology have led to earlier detection of asymptomatic and organ‐confined renal masses of smaller size.…”
supporting
confidence: 80%
“…Second, RNS was significantly correlated with histological findings of renal masses, as previously shown in other studies . Recent advances in imaging technology have led to earlier detection of asymptomatic and organ‐confined renal masses of smaller size.…”
supporting
confidence: 80%
“…A study by Satasivam et al . showed that an increasing RENAL score is associated with histological features of tumor aggressiveness . Ficarra et al .…”
Section: Discussionmentioning
confidence: 99%
“…External validation revealed an area under the curve of 73% for prediction of high-grade disease [40]. Likewise, recent studies showed that higher tumor complexity according to the RENAL score is associated with high-grade disease and clear-cell subtype [41,42]. …”
Section: Evidence Synthesismentioning
confidence: 99%